How to align logistics environmental sustainability with corporate strategy? An Italian perspective - Prataviera, Lorenzo Bruno; Creazza, Alessandro; Perotti, Sara; Rodrigues, Vasco Sanchez (Taylor & Francis, 2025)
Logistics environmental sustainability is a priority for practitioners and policymakers, but companies lack clarity about how to align it with strategic purposes. As this prevents them from coherently turning sustainability into action, this paper focuses on how companies can align logistics environmental sustainability with corporate strategies. We conducted multiple embedded case research involving logistics service providers (LSPs) and shippers operating in the Italian context. We selected 13 companies (6 LSPs and 7 shippers) and conducted semi-structured interviews to contextualise and elaborate the extant theory. Results highlight that companies seem more motivated by the need to comply with regulations or to protect their environmental reputation than by a genuine understanding of the actual need for sustainability. A framework is proposed to foster the alignment of logistics environmental sustainability with corporate strategy, underpinned by five main dimensions: degree of awareness, degree of formalisation, measurement systems, governance and accountability, and budget allocation.
Keywords: Logistics; environmental sustainability; corporate strategy; strategic alignment